Structural behaviour of lightweight modular wall panel with various wall thicknesses - Ling, Raymond Toh Siung, 1993-, author; Shek, Poi Ngian, 1982-, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2016